2009
DOI: 10.1017/s143192760909713x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Nanostructure and Photocatalytic Stability of Mesoporous CuCrO2 Delafossite using Analytical Electron Microscopy

Abstract: Investigating new sources of renewable energy has been a major focus in the scientific community during the last decade and continues to attract much attention [1]. Photovoltaics -used in the conversion of solar energy to electrical power -are considered a promising technology to meet the requirements of a clean, non-fossil fuel in the future. The photoelectrochemical cell (PEC), utilizing semiconducting surfaces for catalysis, has been intensively studied as a method to generate hydrogen (H 2 ). Novel catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…17 PEC response for some Cu delafossites has already been demonstrated. [27][28][29][30] Unfortunately, the efficiencies of these photo-conversion processes are not satisfactory, largely due to the inefficient absorption of visible light. Recent theoretical study has revealed that the poor optical absorption is due to the inversion symmetry of their special crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…17 PEC response for some Cu delafossites has already been demonstrated. [27][28][29][30] Unfortunately, the efficiencies of these photo-conversion processes are not satisfactory, largely due to the inefficient absorption of visible light. Recent theoretical study has revealed that the poor optical absorption is due to the inversion symmetry of their special crystal structure.…”
Section: Introductionmentioning
confidence: 99%